Application of nanoparticles and composite materials for energy generation and storage. Issue 4 (6th December 2019) - Ibrahim, Idowu D.; Jamiru, Tamba; Sadiku, Emmanuel R.; Hamam, Yskandar; Alayli, Yasser; Eze, Azunna A.
Abstract : Transition to renewable and sustainable energy from fossil fuels (natural gas, coal, and oil) has dominated the research cycle. The shift is as a result of increasing population growth, industrialisation, decreasing oil reserves and hazardous environmental impact of energy generation from fossil fuels. The new methods of energy generation demand functional materials that are smart and strong for generation and storage of energy. Polymeric composite materials have been widely used. With the recent material performance demand, there is a need to improve the properties of the composite. The improvement can be achieved by reinforcing with fibres and/or nanoparticles as the matrix alone does not possess the required properties. The influence of incorporating fibres and/or fillers into the polymeric matrix has been largely reported in many studies. Recent advancement in the development and use of polymeric composites and nanocomposites is discussed for energy applications. The discussion includes material property improvements, processing methods and improving interface adhesion that may arise when compounding the materials. Various areas, in the energy sector where these materials, can be used are equally highlighted.